Application of the Family of Sign RCA Models for Obtaining the Selected Risk Measures - Górka, Joanna (Dynamic Econometric Models, 2009)
Accurate modelling of risk is very important in finance. There are many alternative risk measures, however none of them is dominating. This paper proposes to use the family of Sign RCA models to obtain the Value-at-Risk (VaR) and Expected Shortfall (ES) measures. For models from the family of Sign RCA models and AR-GARCH model the one-step forecasts of VaR were calculated based on rolling estimates from the given model using different window sizes. To obtain the VaR and ES measures the filtered historical simulation was used in new version proposed by Christoffersen. The results were verified using backtesting and the loss function.